Depression and its characteristics in childhood and adolescence (Research, Society and Development, 2020)
Currently the accelerated and troubled routine ends up also affecting children and adolescents, who are still unable to develop, express and assimilate what happens to them, internally and externally, understand their pains and suffering; thus, they end up developing mental disorders, such as depression. Given the importance of seeking more information about depression, this study aimed to produce a bibliographic review article on depression in childhood and adolescence and its characteristics. The databases Pubmed (US National Library of Medicine), Scielo (Scientific Electronic Library Online), and Google ScholarⓇ were used in the present study, using the descriptors: depression, psychotropic drugs, mental disorders and psychotherapy. The articles analyzed were written in Portuguese, English and Spanish, for the past 22 years. For the diagnosis of children or adolescents, the clinical investigation has its particularities, the anamnesis must be more in-depth and it must go beyond the parents' complaint and the history of the child or adolescent. During treatments, psychopharmaceuticals can be used, as well as alternative therapies, such as supportive psychotherapy, interpersonal therapy, brief dynamic psychotherapy, behavioral therapy, among others. However, according to studies carried out recently, the use of psychotropic drugs in children and adolescents brings worrying revelations. It is concluded, through the study, that care must be taken both in the diagnosis and in the treatment of depression in children and adolescents.